Cytochrome P4501B1 in bone marrow is co-expressed with key markers of mesenchymal stem cells. BMS2 cell line models PAH disruption of bone marrow niche development functions (2020)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants that are metabolized to carcinogenic dihydrodiol epoxides (PAHDE) by cytochrome P450 1B1 (CYP1B1). This metabolism occurs in bone marrow (BM) mesenchymal stem cells (MSC), which sustain hematopoietic stem and progenitor cells (HSPC). In BM, CYP1B1- mediated metabolism of 7, 12-dimethylbenz[a]anthracene (DMBA) suppresses HSPC colony formation within 6 h, whereas benzo(a)pyrene (BP) generates protective cytokines. MSC, enriched from adherent BM cells, yielded the bone marrow stromal, BMS2, cell line. These cells express elevated basal CYP1B1 that scarcely responds to Ah receptor (AhR) inducers. BMS2 cells exhibit extensive transcriptome overlap with leptin receptor positive mesenchymal stem cells (Lepr+ MSC) that control the hematopoietic niche. The overlap includes CYP1B1 and the expression of HSPC regulatory factors (Ebf3, Cxcl12, Kitl, Csf1 and Gas6). MSC are large, adherent fibroblasts that sequester small HSPC and macrophage in the BM niche (Graphic abstract). High basal CYP1B1 expression in BMS2 cells derives from interactions between the Ah-receptor enhancer and proximal promoter SP1 complexes, boosted by autocrine signaling. PAH effects on BMS2 cells model Lepr+MSC niche activity. CYP1B1 metabolizes DMBA to PAHDE, producing p53-mediated mRNA increases, long after the in vivo HSPC suppression. Faster, direct p53 effects, favored by stem cells, remain possible PAHDE targets. However, HSPC regulatory factors remained unresponsive. BP is less toxic in BMS2 cells, but, in BM, CYP1A1 metabolism stimulates macrophage cytokines (Il1b > Tnfa > Ifng) within 6 h. Although absent from BMS2 and Lepr+MSC, their receptors are highly expressed. The impact of this cytokine signaling in MSC remains to be determined.